Dataset associated with "Could the exception become the rule? "Uncontrollable" air pollution events in the U.S. due to wildland fires" - David, Liji (Colorado State University. Libraries, 2020)
Exceptional events occur when air pollution in a specific location exceeds the National Ambient Air Quality Standards (NAAQS) due to an event that cannot be reasonably attributed to human activities, such as wildland fire. Ground-level ozone (O3) and particulate matter (PM) are EPA criteria pollutants regulated under the NAAQS. Smoke from wildland fires can increase PM and O3 concentrations downwind of fire and impact air quality, visibility, and health. Our analysis shows that the frequency of exceptional event reporting for particulate matter with aerodynamic diameters smaller than 2.5 m or 10 m (PM2.5 and PM10) had increased since 2007 when the air quality standards became more stringent. We also show that wildland fires and windblown dust drive many exceptional events in several EPA regions. We note the importance of growth in the number of exceptional event days due to wildfire smoke in the future due to climate change and point to possible changes to the NAAQS and implementations.
The dataset gives the days when O3, PM2.5, and PM10 exceeded the National Ambient Air Quality Standards and were also flagged for an exceptional event in the Environmental Protection Agency (EPA) Air Quality System (AQS) database over the recent 18-year period (2000-2017). We have connected those day(s) with an exact event (e.g., a specific wildland fire, high wind period, stratospheric O3 intrusion, agricultural or prescribed burn). We have also gathered information on the number of Exceptional Event Demonstrations (EED) along with the total number of days (for each EED) submitted by each state (on a county-by-county basis), and the days that were concurred and denied by EPA. We have also included supporting documents for the exceptional day(s).
Department of Atmospheric Science
Department of Chemistry
Keywords: exceptional event; wildfire; NAAQS; exposure; PM2.5; PM10; standards